Feasibility of a tailored, combined intervention with mind-body elements to prevent burnout in healthcare professionals (LAGOM) in a mixed-methods multicenter single-arm trial - Marleen Schröter; Anna K. Koch; Julia Berschick; Julia K. Schiele; Martin Bogdanski; Melanie Steinmetz; Judith Czakert; Wiebke Stritter; Christian S. Kessler; Georg Seifert (Scientific Reports)
Abstract Healthcare professionals (HCPs) face high occupational stress, rendering them highly vulnerable to burnout. Given the significant individual and societal impacts, there is an urgent need for tailored approaches to prevent burnout. This study investigated the acceptability and feasibility of a person-and organization-directed 9-week program (LAGOM) with mind-body elements designed to mitigate burnout among HCPs. This single-arm, multicenter study employed a mixed-methods sequential explanatory design. Descriptive analyses evaluated recruitment, adherence, attrition, data collection completeness, and safety. A pre-post online survey assessed demographic and occupational variables, burnout symptoms (using the Maslach Burnout Inventory) and work-related self-efficacy (using the German BSW-5 questionnaire). The feasibility of electrophysiological measures like pulse and respiration activity was assessed. Semi-structured interviews with a subgroup were qualitatively analyzed following a qualitative content analysis approach. Pre to post changes in burnout symptoms and self-efficacy were exploratively analyzed with paired sample t-tests. Out of 29 HCPs screened, 24 (91.3% females, 65.2% nurses, 26.1% physicians) working at the Charité – Universitätsmedizin Berlin or the Immanuel Hospital Berlin, were included. The drop-out rate was 8%, intervention adherence was 79%. Of training completers, 86% filled out the post-assessments and 94.7% would recommend the program. Pre-post exploratory analyses revealed improvement on burnout scales emotional exhaustion (∆±SD=-2.79 ± 5.63, Cohen´s d = 0.5, 95% Confidence Interval (CI) 0.01;0.97), depersonalization (∆±SD=-1.47 ± 3.20, d = 0.46, 95%CI -0.02;0.93), personal accomplishment (∆±SD = 0.16 ± 3.93, d = 0.04, 95%CI -0.41;0.49), and work-related self-efficacy (∆±SD = 0.17 ± 0.39, d = 0.43, 95%CI -0.05;0.90). Semi-structured interviews (n = 4) revealed that participants valued the course content and collegial exchange but suggested allowing more time for discussion and reducing theoretical input. Electrophysiological measures (n = 14) were deemed feasible. The study supports the acceptability and feasibility of implementing LAGOM in the healthcare setting, with initial indications of effectiveness. Program sessions need to be modified to increase time for participant exchange. Securing visible leadership commitment and sufficient resources will be critical for future success. Trial Registration: German Clinical Trials Register: DRKS00032014, registered 17/10/2023, https://drks.de/search/de/trial/DRKS00032014.